2022
DOI: 10.1002/marc.202200761
|View full text |Cite
|
Sign up to set email alerts
|

Induced Smectic E Phase in a Binary Blend of Side‐Chain Liquid Crystalline Polymers

Abstract: Two liquid crystalline polymers containing an azobenzene or cyanobiphenyl mesogenic side chain that adopt smectic A phases are mechanically mixed at 1:1 mesogen molar ratio at an isotropic phase temperature and then cooled. The resultant binary polymer mixture behaves like a single component as revealed by polarized microscopy observation and differential scanning calorimetry, indicating that the binary mixture forms a fully compatible polymer blend. Moreover, the simple polymer blend unexpectedly leads to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The Miller indices were obtained from the intersection of the Debye–Scherrer rings superimposed on the reciprocal lattice plane . Considering the wide-angle scattering at q = 15 nm –1 in the SWAXS patterns, the smectic A (SmA)- and smectic B (SmB)-like phases are observed at 120 and 70 °C, respectively (Figure c). Obviously, C1PAz forms a more ordered self-assembly packing state compared with that of C2PAz. Particularly, when depicting the self-assembling structure by considering the values of lattice constants a and b , the main-chain distance is reduced and the side-chain mesogens further interdigitate in the SmB-like phase.…”
Section: Resultsmentioning
confidence: 99%
“…The Miller indices were obtained from the intersection of the Debye–Scherrer rings superimposed on the reciprocal lattice plane . Considering the wide-angle scattering at q = 15 nm –1 in the SWAXS patterns, the smectic A (SmA)- and smectic B (SmB)-like phases are observed at 120 and 70 °C, respectively (Figure c). Obviously, C1PAz forms a more ordered self-assembly packing state compared with that of C2PAz. Particularly, when depicting the self-assembling structure by considering the values of lattice constants a and b , the main-chain distance is reduced and the side-chain mesogens further interdigitate in the SmB-like phase.…”
Section: Resultsmentioning
confidence: 99%
“…Polarized light microscopy (PLM) is an effective tool for studying the morphology of polymers, providing visual insights into the characteristic structural elements of polymer units [ 21 , 22 , 23 , 24 ]. PLM allows for the observation of the shapes of polymer spherulites.…”
Section: Resultsmentioning
confidence: 99%
“…in the high-angle region assigned as ( 110), ( 111), (200), and (210) diffractions of SmE with a and b values of 0.81 and 0.52 nm, 41,[43][44][45][46] respectively. Furthermore, a simple smectic phase structure of smectic A (SmA) or smectic C (SmC) could be confirmed for P-2 at higher temperatures, as indicated by the diffraction peak at 2.41 nm À1 in the low-angle region and the diffused high-angle amorphous broad halo.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…To sum up, considering the similarity of the diffraction peaks at the high-angle region of sample P-2 to that of polymer P-3 (referenced to as PMMS-X Chol -0.00 in ref. 41), we concluded that the self-assembly structure of P-2 at low temperatures could be smectic E (SmE), evidenced by the five diffraction peaks in the low-angle region assigned as (001), (002), ( 003), (004), and (005), as well as the four diffraction peaks in the high-angle region assigned as ( 110), ( 111), (200), and (210) diffractions of SmE with a and b values of 0.81 and 0.52 nm, 41,[43][44][45][46] respectively. Furthermore, a simple smectic phase structure of smectic A (SmA) or smectic C (SmC) could be confirmed for P-2 at higher temperatures, as indicated by the diffraction peak at 2.41 nm À1 in the low-angle region and the diffused high-angle amorphous broad halo.…”
Section: Papermentioning
confidence: 99%